A General Discrete Time Model of Population Dynamics in the Presence of an Infection - Giuseppe Izzo; Yoshiaki Muroya; Antonia Vecchio (Discrete Dynamics in Nature and Society)
We present a set of difference equations which generalizes that proposed in the work of G. Izzo and A. Vecchio (2007) and represents the discrete counterpart of a larger class of continuous model concerning the dynamics of an infection in an organism or in a host population. The limiting behavior of this new discrete model is studied and a threshold parameter playing the role of the basic reproduction number is derived.